Pattern of Aedes aegypti and Aedes albopictus Associated with Human Exposure to Dengue Virus in Kinshasa, the Democratic Republic of the Congo - Kennedy Makola Mbanzulu; Roger Wumba; Leonard E. G. Mboera; Jean-Marie Ntumba Kayembe; Danoff Engbu; Michael Mondjo Bojabwa; Josué Kikana Zanga; Gerald Misinzo; Sharadhuli Iddi Kimera (Tropical Medicine and Infectious Disease, 2022)
Dengue is a worldwide public health concern. The current study assessed the extent of human exposure to the dengue virus in relation to the distribution pattern of Aedes aegypti and Ae. albopictus in Kinshasa. Cross-sectional surveys were carried out in 2021 and 2022. The baseline entomological survey involved 19 municipalities using a grid cell sampling approach. All containers holding water were inspected for the presence of larvae in each grid. The collected larvae were kept in an insectary until the adult emergence for morphological identification. Four hundred febrile patients attending the hospital were screened for the presence of dengue antibodies (IgG, IgM) and NS1 antigen using a rapid diagnostic test (RDT) Biosynex®. Residences of positive cases were geo-referenced. We evaluated 1850 grid cells, of which 19.5% were positive for Aedes larvae. The positive grid cells were identified in the Ndjili (44.0%), Mont Ngafula (32.0%) and Ngaliema (26.0%), and Limete (32.0%) municipalities. The Ae. aegypti (11.2%) predominated in the northwestern, and Ae. albopictus (9.1%) appeared in the high vegetation coverage areas. Of 61 (15.3%) participants exposed to dengue, 8.3% presented acute dengue. Young, (6–17 years), male, and Mont Amba district participants were most exposed to dengue. In conclusion, dengue occurrence in Kinshasa overlaps somewhat the geographical and ecological distributions of Ae. aegypti and Ae. albopictus. Both species are not homogenously distributed, likely due to environmental factors. These findings can assist the targeted control activities.